From Big Oil to Big Green Holding the Oil Industry to Account for the Climate Crisis - Grasso, Marco (The MIT Press, 2022)
How Big Oil can transform itself into Big Green through reparation and decarbonization to rectify the harm it has done through fossil fuels. In From Big Oil to Big Green, Marco Grasso examines the responsibility of the oil and gas industry for the climate crisis and develops a moral framework that lays out its duties of reparation and decarbonization to allay the harm it has done. By framing climate change as a moral issue and outlining the industry's obligation to tackle it, Grasso shows that Big Oil is a central, yet overlooked, agent of climate ethics and policy. Grasso argues that by indiscriminately flooding the global economy with fossil fuels-while convincing the public that halting climate change is a matter of consumer choice, that fossil fuels are synonymous with energy, and that a decarbonized world would take civilization back to the Stone Age-Big Oil is morally responsible for the climate crisis. He explains that it has managed to avoid being held financially accountable for past harm and that its duty of reparation has never been theoretically developed or justified. With this book, he fills those gaps. After making the moral case for climate reparations and their implementation, Grasso develops Big Oil's duty of decarbonization, which entails its transformation into Big Green by phasing out carbon emissions from its processes and, especially, its products.